2009
DOI: 10.5694/j.1326-5377.2009.tb02619.x
|View full text |Cite
|
Sign up to set email alerts
|

Teams communicating through STEPPS

Abstract: Objective: To evaluate the effectiveness of the implementation of a TeamSTEPPS (Team Strategies and Tools to Enhance Performance and Patient Safety) program at an Australian mental health facility. Design, setting and participants: TeamSTEPPS is an evidence‐based teamwork training system developed in the United States. Five health care sites in South Australia implemented TeamSTEPPS using a train‐the‐trainer model over an 8‐month intervention period commencing January 2008 and concluding September 2008. A team… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
73
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 11 publications
2
73
0
Order By: Relevance
“…All studies were published in English. One study was Swiss,24 one was Australian,37 and two were British 28 38. The rest were American.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All studies were published in English. One study was Swiss,24 one was Australian,37 and two were British 28 38. The rest were American.…”
Section: Resultsmentioning
confidence: 99%
“…All studies except two19 36 described a process of training needs assessment, the main method being a safety or teamwork attitude questionnaire (SAQ/TAQ), use of patient safety data and inputs from staff. The duration of the course varied from 4 h to 3 days (a few also described longer train-the-trainer courses) 26 31 37 39. All interventions focused on teamwork, coordination and communication.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, studies evaluating interventions that aim to improve safety culture have shown increases in safety climate scores,29–35 while one study also reported improved observed safety behaviour and performance 36. Unfortunately, these studies either had uncontrolled pre-post designs, small sample sizes of selected participants or were case reports from single healthcare organisations 37.…”
Section: Discussionmentioning
confidence: 99%